Self-Perception of the Ethical Leadership Exercise of University Leaders - Unda, Sofía (International Journal of Educational Leadership and Management, 2017)
There is a clear shortage in academic research on ethical leadership, especially at an educational context, whatever its level. Therefore, it has been detected the need for a specific research on how university managers perceive themselves exercising their ethical leadership in such a context. In this sense, this work offers definite results obtained through the research developed in April 2013 with 31 university managers working in Social Councils, University Boards as well as other university teams, both at public and private national universities all over Spain. These results have shown that their self-perceptions are basically supported by a positive conception of their decisions. In fact, 20 out of 29 university managers interviewed have declared being totally aware of the integrity of their decision-making processes. They had been previously interviewed through semi-structured surveys whose contents have been analyzed according to the ATLAS.ti.7 Program. Finally, by means of a mixed-analytical strategy previous codes were defined and structured, in order to organize the answers given by the university managers, whilst new codes were emerging from the discussion. As a result, five general codes defining the appropriate categories for university managers' self-perception were analyzed in detail: a) positive self-perception, b) positive but partial self-perception, c) negative self-perception/cooperative, d) negative self-perception/leader and e) unable to self-perception.
Keywords: ethical leadership; university management; self-perception; Emerging